DAMPAK PROFITABILITAS, ALIRAN KAS BEBAS, DAN KESEMPATAN INVESTASI TERHADAP PEMBAYARAN DIVIDEN PERUSAHAAN PERBANKAN - Salvatore Wika Lingga Pradana; I Putu Sugiartha Sanjaya (University of Merdeka Malang, 2017)
This study aimed to identify and analyze the factors that affected paid dividend proxies by Dividend Payout Ratio (DPR) on the banking companies listed in Indonesia Stock Exchange (IDX). Multiple regression was a model of analysis that was used by the researchers to examine several variables which might affect the dividend payout ratio such as profitability, free cash flow, and investment opportunity set as independent variables, as well as firm size as a control variable. The samples in this study were 29 conventional banks that were listed in the Indonesia Stock Exchange (IDX). The result showed that the independent variable profitability (ROA) had a significant and positive effect on the dividend payout ratio while the free cash flow variable and the investment opportunity set did not affect the dividend payout ratio. Control variables firm size had a significant and negative effect on the dividend payout ratio.